A new species of Trechisibus from Peruvian Andes (Coleoptera: Carabidae, Trechinae) - Delgado Mamani, Pedro Ernesto (2016)
[EN] In this work the new species Trechisibus (s. str.) delestali sp. n., is described from the southern Peruvian Andes. The morphological differences with the geographically closest species of the subgenus are also presented and discussed.